Survey of Availability, Use and Knowledge about Toxicity of Diphenhydramine for Children among Iranian Mothers: Mothers Knowledge about Toxicity of Diphenhydramine for Infants - Karim Ebrahim,; Maryam Nakhjavani, (Iranian Journal of Pharmaceutical Sciences, 2013)
Diphenhydramine, as an antihistamine drug is widely used for the treatment of allergies. However, being classified as an over the counter medication and the general belief on the low adverse effect profile of this drug has made it widely accessible to the families. Recent reports of diphenhydramine intoxication and mortality, noticeably in children and infants have raised some serious concerns. In the present study, 241 mothers who referred to four different regional locations of mother and child health care service centers were asked to fill up a questionnaire on diphenhydramine. The results of our study showed that besides the lack of adequate information on the indications and safety of the drug, 97% of the mothers used this medication for different illness conditions of the children, with more than 20% misindications on respiratory infections, fever and pain conditions. More than 40% of mothers did not have specific idea about the age related restrictions of the medication and 81% had no information on the proper dose indication. Furthermore 86% of mothers had no information about its adverse effects and the rest of them knew only about drug induced drowsiness. The results of this study show that diphenhydramine usage should be more closely observed, the pharmacists should make consult families before providing them with diphenhydramine, the pharmaceutical companies should be obliged to provide a drug information sheet in the packaging, and the public media and various health care providers should also feel responsibility to forewarn mothers about the results of self-prescribed medication.